Der Einfluß natürlicher und wirtschaftlicher Standortfaktoren auf die räumliche Ordnung der Landwirtschaft - dargestellt am Beispiel der Ausbreitung des Gemüsebaus in Venezuela - Waldt, Hans-Otto (ERDKUNDE, 1979)
Until the thirties of this century the supply of fresh vegetables to Caracas and the remaining towns of the country was possible only from the surrounding areas of these places, since the easily perishable products were unable to stand longer transportation on roads which were then in a poor condition. It was only with the improvement of roads and speedier transportation that it became feasible to take up the cultivation of vegetables at greater distances from the market. Since then production has increasingly shifted to locations which offer the best natural conditions for specific crops. The shift of locations at greater distances from the market also results in rising transport costs, however, so that extensification of cultivation must be the next step if it is to be carried out with its full economic consequences. The size of holdings and the degree of mechanization do in fact increase with growing distance from the capital. In connection with it there is an expansion of acreage under potato cultivation at the expense of those sorts of vegetables which do not permit effective employment of machinery. In this process a transition can be discerned, leading from market gardening via vegetable farming to potato monoculture. The zonal succession of progressively more extensive types of farming, however, becomes more diffused with growing distance from the capital, since its influence becomes increasingly superimposed by the influences of the country’s remaining towns.